Moringa gum and its modified form as a potential green polymer used in biomedical field. (1st December 2020) - Badwaik, Hemant Ramachandra; Hoque, Ashique Al; Kumari, Leena; Sakure, Kalyani; Baghel, Madhuri; Giri, Tapan Kumar
Highlights: Moringa oleifera gum is one of the emerging natural polymer. Moringa gum comprises of (1, 6), (1, 3) and (1, 3, 6) β glycosidic linkages. Moringa gum & derivatives employed in various industrial and biomedical fields. Abstract: Over the past few decades, natural gums are extensively investigated by the researchers due to their beneficial physicochemical properties. Among them, the polysaccharide exudates obtained from the stem of the plant Moringa oleifera, known as moringa gum, is investigated widely in the food, pharmaceutical, and other areas. The moringa gum is used in the form of dried powder as a pharmaceutical excipient in various formulations. It is also derivatized either by grafting or by other chemical modifications for enhancing its properties. The research on moringa gum and modified moringa gum has diversified in numerous biomedical fields. However, summarization of these progress are not available in the literature. This article gives an overview of the collection, purification, structural elucidation, and modification of moringa gum. Moreover, the present review furnishes complete information on the various aspects of moringa gum and its applications in various industrial and biomedical fields.